Ketogenic diet and metabolic health: A review of its impact on type 2 diabetes and obesity. Analysis of research on the ketogenic diet in the context of treating metabolic disorders - Paweł Nojek; Monika Zawół; Mariusz Zimonczyk; Wiktoria Pawlik; Agnieszka Nowotarska; Gustaw Błaszczyński (Kazimierz Wielki University, 2024)
This paper aims to review current research on the ketogenic diet as a potential therapeutic approach for obesity and type 2 diabetes. This diet is characterized by high fat intake, moderate protein, and minimal carbohydrates, leading to a state of ketosis in which the body utilizes ketone bodies as its primary energy source. Studies indicate that the ketogenic diet may positively influence blood glucose control, enhance insulin sensitivity, and facilitate weight reduction, particularly relevant in the context of insulin resistance. The paper discusses the biological mechanisms underlying these effects, as well as potential risks associated with long-term adherence to the diet. It underscores that, despite promising results, further research is necessary to better understand the long-term effects of the ketogenic diet and its applicability across various patient populations. Conclusions highlight the need for patient monitoring during the dietary regimen and the potential for integrating the ketogenic diet into a broader strategy for managing metabolic diseases